IMPACT OF DIABETES ON HEART RATE VARIABILITY IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Saleem, Shemaila; Majeed, Syed Muhammad Imran (Journal of Ayub Medical College Abbottabad, 2012)
Background: Diabetes is a well-known cause of sudden mortality. Due to autonomic imbalance, those patients who are suffering from ischemic heart disease and diabetes concurrently are at a greater risk of manifesting arrhythmias. Heart rate variability (HRV) can be utilised for assessment of autonomic nervous system. The purpose of this study was to identify the values of HRV in diabetic and non-diabetic patients with acute myocardial infarction (AMI). Methods: This noninterventional descriptive study was carried out at Armed Forces Institute of Cardiology over a period of 6 months. A total of 50 healthy volunteers and 50 patients with myocardial infarction (MI) were Holter monitored for 24 hours and HRV was analysed in time and frequency domains. Results: The time domain indices; SDNN (non diabetics=78±30 ms vs diabetics=58±20 ms; p=0.01), SDANN (non diabetics=68±28 ms vs diabetics=49±19 ms; p=0.23), SDNNi (non diabetics=36±13 ms vs diabetics=26±14 ms; p=0.02), RMSSD (non diabetics=29±11 ms vs diabetics=23±15 ms; p=0.16) and pNN50 (non diabetics=7±10 ms vs diabetics=4±12 ms; p=0.43) were declined in diabetic patients with acute myocardial infarction when compared with non diabetic patients inflicted with infarction. Frequency domain indices, Total power (non diabetics=1479±12 ms2 vs diabetics=759±6 ms2, p=0.01), VLF (non diabetics=997±9 ms2 vs diabetics=495±5 ms2, p=0.04), LF (non diabetics=292±2 ms2 vs diabetics=123±1 ms2, p=0.01) and HF (non diabetics=121±1 ms2 vs diabetics=54±5 ms2, p=0.01) showed attenuated HRV in diabetic patients with acute myocardial infarction. Comparison of diabetic and non diabetic infracted patients with healthy volunteers revealed decreased HRV in patients with myocardial infarction but gets even worse in diabetic patients with myocardial infarction. Conclusions: Heart rate variability is attenuated in diabetic patients with acute myocardial infarction. It reflects sympatho-vagal imbalance in coronary patients with co-existent diabetes mellitus. Keywords: Autonomic nervous system, diabetes mellitus, ambulatory electrocardiography